THE EFFECT OF WORK ENVIRONTMENT ON TEACHERS’ PERFORMANCE AT SMA NEGERI 1 DULUPI - Nur Rahmi (Universitas Muhammadiyah Kalimantan Timur, 2020)
This study was conducted to determine how much the Physical Work Environment (X1), Non-Physical Work Environment (X2) affect, both simultaneously and partially, teachers’ performance (Y) at SMA Negeri 1 Dulupi. This study used quantitative method and the data collection was carried out by using a questionnaire instrument. The analysis techniques used in this study was Path Analysis. From the research results, it was found that the Physical Work Environment and Non-Physical Work Environment simultaneously affected teachers’ performance (Y) at SMA Negeri 1 Dulupi with a value of 0.715 (71.5%). The Fcount showed a result of 14.268 while the Ftable was 3.25 and the probability sig 0.000 < probability ɑ = 0.05. This means that at the 95% confidence level, the Work Environment variable (X), which consists of the Physical Work Environment (X1) and the Non-Physical Work Environment (X2), has a positive and significant effect on Teachers’ Performance (Y). Partially, the physical work environment has a positive and significant effect on teachers’ performance of 0.619 (61.9%), and the non-physical work environment partially has a positive and significant effect on teachers’ performance of 0.247 (24.7%).